The construction of a precision conductance bridge and its application to a study of chromium sulphate complexes - Goddard, Errol Desmond (Rhodes University, Faculty of Science, Department of Chemistry, 1949)
A constant temperature room employing the comparatively new method of temperature control by means of a thyratron relay has been constructed. A high precision conductance bridge has been built in a very convenient form. Improvements include the incorporation of a cathode ray oscilloscope as null detector and the inclusion of a very stable oscillator of the phase shift type which is capable of giving a very pure wave form. Tests carried out on a system of degenerative tuning showed the the system is not easily applicable to high gain amplifiers. A new form of conductometric titration cell, employing the dipping type electrodes has been designed with special precautions against possible Parker Effect. A series of tests has been carried out on three types of cell to ascertain the effects of absorption, polarisation and Parker Effect on the accuracy of an ordinary conductometric titration. Conductometric titrations of NaOH solutions of violet and green chromic sulphate has been carried out, and the effect of aging these solutions closely studied. In addition, conductometric titrations of BaCLâ‚‚ into the chromic solutions have been made, and the NaOH titrations have been studied potentiometrically as well.
Keywords: Chromium